2007
DOI: 10.1111/j.1469-8137.2007.02239.x
|View full text |Cite
|
Sign up to set email alerts
|

The cellular and molecular biology of conifer embryogenesis

Abstract: 511 Review SummaryGymnosperms and angiosperms are thought to have evolved from a common ancestor c . 300 million yr ago. The manner in which gymnosperms and angiosperms form seeds has diverged and, although broad similarities are evident, the anatomy and cell and molecular biology of embryogenesis in gymnosperms, such as the coniferous trees pine, spruce and fir, differ significantly from those in the most widely studied model angiosperm Arabidopsis thaliana . Molecular analysis of signaling pathways and proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(81 citation statements)
references
References 213 publications
(171 reference statements)
0
81
0
Order By: Relevance
“…Arabidopsis genes related to embryogenesis, 85% had a strong sequence similarity to an expressed sequence tag in the loblolly pine (Pinus taeda) database (Cairney and Pullman 2007). However, it is important to gain knowledge about the temporal and spatial expression pattern for different genes in order to understand the fundamentals of embryogenesis in conifers.…”
Section: Communicated By P Ingvarssonmentioning
confidence: 99%
“…Arabidopsis genes related to embryogenesis, 85% had a strong sequence similarity to an expressed sequence tag in the loblolly pine (Pinus taeda) database (Cairney and Pullman 2007). However, it is important to gain knowledge about the temporal and spatial expression pattern for different genes in order to understand the fundamentals of embryogenesis in conifers.…”
Section: Communicated By P Ingvarssonmentioning
confidence: 99%
“…In conifer seeds, similar kind of recognition may take place between the megagametophyte and embryos during the different stages of embryogenesis. Expressed sequence tags (ESTs) of loblolly pine (Pinus taeda L.) embryos 36 together with identified loblolly pine microRNAs (miRNAs) that modulate in the megagametophyte and zygotic embryo stage-specifically will help to unravel the actual signal cascades directing the development of different conifer seed tissues.…”
Section: Exploring the Evolution And Genetic Regulation Of Life And Dmentioning
confidence: 99%
“…The number of transcribed genes appears to be 30 to 40 % larger than in any other tissue (Cairney and Pullman 2007;Yakovlev et al 2014) with high relevance to the gene network in A. thaliana (300-450 genes, Cairney and Pullman 2007;Zhang et al 2012a). Transcript profiles during zygotic embryogenesis are highly correlated between Pinus pinaster and A. thaliana, with only 3 % of the transcripts estimated to be gymnosperm-specific (de Vega-Bartol et al 2013).…”
Section: Conifer Embryo Developmentmentioning
confidence: 97%
“…Transcript profiles during zygotic embryogenesis are highly correlated between Pinus pinaster and A. thaliana, with only 3 % of the transcripts estimated to be gymnosperm-specific (de Vega-Bartol et al 2013). Differences between angiosperms and gymnosperms are thought to arise principally from spatiotemporal variations in gene expression resulting partly from epigenetic modifications, which may act as an adaptive mechanism in such long-lived species (Cairney and Pullman 2007;Vestman et al 2011;de VegaBartol et al 2013). Yakovlev et al (2014) specifically reported temperature-dependent differential transcriptomes in Picea abies embryogenic masses potentially associated with the formation of an epigenetic memory, with a delayed, persistent impact on seedling growth.…”
Section: Conifer Embryo Developmentmentioning
confidence: 99%